Just Institutions or just Institutions? Research on Groundwater Justice in the European Union - Jakob Kramer (International Journal of the Commons, 2025)
This qualitative systematic literature review examines discussions on groundwater justice in the European Union (EU) by analyzing 51 peer-reviewed academic articles that address groundwater governance and justice-related issues. The review identifies a limited number of studies that explicitly focus on groundwater justice, with most research emphasizing the local and regional institutional setup for groundwater distribution, particularly in agricultural contexts in Spain and France. Key themes in the literature include the role of institutions in regulating groundwater distribution, decision-making processes, and the recognition of different forms of knowledge. The literature also examines groundwater markets, often in relation to their potential to exacerbate inequalities, and explores the historical development of groundwater rights regimes, highlighting their continued influence on governance and water rights regimes. Additionally, studies discuss how infrastructure investments can further amplify inequalities, particularly as groundwater levels decline. The limited explicit focus on groundwater justice in the EU may be linked to disciplinary traditions in commons scholarship and environmental justice research that tend to focus on institutions and high-profile cases of injustices, respectively. This paper highlights how grounded justice perspectives from EJ and Water justice literature based on capabilities and power can analyze more subtle cases of injustice. The review suggests that integrating uncertainty as an analytical category might be fruitful for groundwater justice research since uncertainties regarding groundwater materiality and modelling ultimately influence institutions mediating groundwater access and decision-making processes. Future research could therefore explore the relationship between uncertainty and justice, specifically how uncertainties shape groundwater rights distributions and decision-making processes.